TURNING POINTS OF LIVING TOGETHER CULTURE IN ISLAMIC SOCIETY - Kemal GÖZ (Fırat University, 2019)
Man who has to live in community has to obey some rules. Living in community described as a ball of relationships between humans, makes inevitable to have duties and responsibilities in those relationships. Love, respect, tolerance, brotherhood, helping each other, solidarity, equality, righteousness, freedom, and justice are the properties that i